Фінансово-кредитний механізм зовнішньоекономічної діяльності - Демченко, Іван Володимирович; Демченко, Иван Владимирович; Demchenko, Ivan (Мелітополь: ТДАТУ, 2018)
UK: Рівень розвитку економіки любої країни тісно корелює зі ступенем її відкритості, скільки тісна інтеграція учасників світового фінансового простру надає низку перспектив та переваг. Проте запорукою ефективного провадження зовнішньо-економічної діяльності стають елементи фінансово-кредитного механізму. Саме фінансово-кредитний механізм створює умови, згладжує зовні виклики та опосередковано забезпечує дотримання вимог уряду щодо конкретних суб’єктів зовнішньоекономічної діяльності. EN: At various stages of the formation of the financial regulation system, the degree of state influence on economic processes was different and was accompanied by a change in the forms, methods and levers of economic management. The functioning of the financial mechanism of state regulation is conditioned by the need for the state to carry out an economic function, establishing and maintaining the optimal structure of the national economy, identifying the priority directions of economic development, forming and further improving the institutional support of the socio-economic sphere, improving the welfare of the population and providing it with appropriate social services, support sufficient level of employment of the population. The purpose of the study is to substantiate the essence and content of the financial and credit mechanism of external activity and to elaborate on the details of the manifestation of its separate elements and subsystems in conditions of Ukraine's rapid integration into the global economic environment. Conclusions. Foreign economic activity is intended to ensure the economic development of subjects and manifests itself in the context of appropriate regulation. The peculiarity of foreign economic activity is the search for optimal directions of interaction of the economy and preservation of the interests of individual participants in foreign economic operations. Financial-credit and tax regulation of foreign-economic activities should be called the priority directions of development of both individual entities and the state as a whole.
Keywords: фінансово-кредитний механізм; регулювання; економчний розвиток; суб’єкти ЗЕД; фінансові важелі; фінансові методи; financial and credit mechanism; regulation; economic development; subjects of foreign economic activity; financial levers; financial methods; foreign economic activity